Differentiation of Arrhythmias by Measurement of Intracardiac Pressures in Man. - Beauregard LM; Volosin KJ; Waxman HL (Pacing & Clinical Electrophysiology, 1991)
Antitachycardia devices currently use sustained high rate, abrupt changes in cycle length, and probability density function to determine the onset of ventricular tachycardia. Hemodynamic changes occur with the onset of tachycardia and may provide a method of discriminating supraventricular from ventricular tachycardia. In this study, patients had atrial and ventricular pressures measured during rapid atrial and ventricular pacing. Right atrial pressure increased significantly with ventricular pacing but not with atrial pacing, flight ventricular pressures did not significantly differ with atrial or ventricular pacing. The change in atrial pressure compared to baseline was greater, with ventricular pacing compared to atrial pacing. Right ventricular pressure increased compared to baseline with atrial or ventricular pacing, but there was no significant difference between pacing modalities. Measurement of right atrial pressure might prove useful in discriminating supraventricular from ventricular tachycardia.